2017
DOI: 10.1186/s13756-017-0223-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for surgical site infections in obstetric and gynecological surgeries from a teaching hospital in rural India

Abstract: BackgroundSurgical site infections (SSI) are one of the most common healthcare associated infections in the low-middle income countries. Data on incidence and risk factors for SSI following surgeries in general and Obstetric and Gynecological surgeries in particular are scare. This study set out to identify risk factors for SSI in patients undergoing Obstetric and Gynecological surgeries in an Indian rural hospital.MethodsPatients who underwent a surgical procedure between September 2010 to February 2013 in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
40
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 29 publications
12
40
1
5
Order By: Relevance
“…In this study, the majority of cases (55%) of SSI were above 25years age and this was statistically signi cant. This was similar to studies conducted by Anjum et al and Wloch C.et al (2012), while a study was done by Olicer Ezechi et al (2009) in Nigeria showed 75% SSI cases below 25years age, replicating the outcomes from the study by Ashish Pathak et al (2017) in rural India [8][9][10]. A few have also reported an absence of any association between maternal age and SSI [3,18].…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the majority of cases (55%) of SSI were above 25years age and this was statistically signi cant. This was similar to studies conducted by Anjum et al and Wloch C.et al (2012), while a study was done by Olicer Ezechi et al (2009) in Nigeria showed 75% SSI cases below 25years age, replicating the outcomes from the study by Ashish Pathak et al (2017) in rural India [8][9][10]. A few have also reported an absence of any association between maternal age and SSI [3,18].…”
Section: Discussionsupporting
confidence: 88%
“…In present study, the prevalence of surgical site infections among obstetric and gynaecological surgeries was 10%. In a study by Pathak et al [12], the cumulative incidence rate of SSI was 7.84% (95% CI 6.30-9.38) while Shahane V et al [10] and Nisa MN et al [14] observed the cumulative incidence as 6% and 6.5% respectively.…”
Section: Discussion:-mentioning
confidence: 99%
“…An explanation for risk for SSI following blood transfusion remains unclear and probably reflects a proxy for severe anemia and consequent low oxygen carrying capacity and delivery to the tissues, potential contamination, and transfusion related immunomodulation in presence of critical illness. 33,34 A previous study showed a predominance of SSI in the age group >65 years compared to <65 years. 35 We found a significantly higher rate of SSI in emergency operations compared to routine elective surgeries, (11.9% versus 4.4%; P < 0.05).…”
Section: Discussionmentioning
confidence: 99%